2001
DOI: 10.1542/peds.108.3.608
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Infectious Diseases Among Internationally Adopted Children

Abstract: We demonstrated increased rates of latent tuberculosis infection and G lamblia infection than previously reported. Thus, ongoing surveillance of internationally adopted children, international trends in infectious diseases, and appropriate screening will ensure the long-term health of adopted children as well as their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
132
7
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(151 citation statements)
references
References 18 publications
9
132
7
3
Order By: Relevance
“…PCR analysis with the bla SHV primers showed the presence of a 795-bp fragment only in the seven serotype Babelsberg ESBL-producing isolates and in all the serotype Enteridis isolates. The sequence from both strands of PCR 21 isolates. Sequencing of the entire nucleotide sequence from both strands in isolate 2 identified bla TEM-1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR analysis with the bla SHV primers showed the presence of a 795-bp fragment only in the seven serotype Babelsberg ESBL-producing isolates and in all the serotype Enteridis isolates. The sequence from both strands of PCR 21 isolates. Sequencing of the entire nucleotide sequence from both strands in isolate 2 identified bla TEM-1 .…”
Section: Resultsmentioning
confidence: 99%
“…Several reports from U.S. authors indicated that children adopted from abroad are at increased risk of infections acquired in their country of origin (7,21). In these studies, the adopted children rarely had infections with Salmonella (less than 2%) compared to tuberculosis or hepatitis B, but none of the children were adopted from Africa.…”
Section: Discussionmentioning
confidence: 97%
“…23 Several investigators have evaluated international adoptees for LTBI and TB disease. Saiman et al 24 performed TSTs on 404 internationally adopted children; 19% (75 of 404) had positive TSTs (TST Ն 10 mm) and normal chest radiographs. In contrast, previous rates of LTBI among international adoptees ranged from 0.6% to 5%.…”
Section: International Adoption Of Childrenmentioning
confidence: 99%
“…Adoptive parents, adoption agencies, and physicians who care for internationally adopted children have wondered whether the young age at placement and residence in foster care (rather than orphanages) reduce the frequency of health and developmental issues such as those described in children who are adopted from Russia, Romania, China, and other countries. [2][3][4][5][6][7][8][9][10][11][12] Other speculations include the possibility that Guatemalan children are less likely to be exposed prenatally to drugs or alcohol than children from other regions and that their vaccine records are more "believable" than those from some other countries. 13 Moreover, although foster care is widely believed to result in better health and developmental status for children without parents, a direct comparison of the status of children who are raised by these 2 methods of care has not previously been reported.…”
mentioning
confidence: 99%